KEBIJAKAN PEMERINTAH TERHADAP PPKM DALAM MASA PANDEMIC COVID-19 DI LUAR PULAU JAWA DAN BALI BERDASARKAN INSTRUKSI MENTERI DALAM NEGERI NO 31 TAHUN 2021 - Kunto Fitricia Elfisa Irian (Fakultas Hukum Universitas Tarumanagara, 2021)
This paper is based on the current situation where there are many pros and cons regarding the Implementation of Restrictions on Community Activities. PPKM is a policy carried out by the government due to a new wave in the COVID-19 pandemic in Indonesia or the increasing number of people who are positively affected by COVID-19 in Indonesia. PPKM itself does not only apply in Java-Bali but also applies in Kalimantan, Sumatra, Nusa Tenggara, Maluku and Papua, PPKM also continues to be extended over time followed by various levels ranging from 1-4 according to the slump that occurred in the community. In the Instruction of the Minister of Home Affairs No. 31 of 2021, it is stated that following up the directives of the President of the Republic of Indonesia to implement the Implementation of Level 4 (four) CoronaVirus Disease (COVID-19) Restrictions on Community Activities in Sumatra, Kalimantan, Sulawesi, Nusa Tenggara, and Papua with criteria for level 4 (four) pandemic situations based on an assessment by the Ministry of Health. This research method is carried out using the Normative Research method by reviewing the laws and regulations relating to PPKM policies in Indonesia specifically outside the islands of Java and Bali.